(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The most volatile organic compounds contaminating ground water and agricultural waste waters are chlorinated hydrocarbons and aromatic substances. It’s better to recover the dissolved compounds in the water to resolve the issue. The equilibrium adsorption was studied in order to determine the capacity for recovery with volatile organic water compounds of granular activated carbon (GAC). This research focuses on the adsorption of dichloromethane in a commercial GAC as a conventional chlorinated organic volatile compound, and toluene as an aromatic organic fluid compound representative. Together with toluene in 293, 303 and 313 K and dichloromethane in 298, 303 and 313 K inside the solubility spectrum, the two volatile organic compounds on GAC were assessed at 3 separate temperatures. GAC adsorption was 4 and 0,2 molKg-1 respectively, with a combined adsorption capacity of dichloromethane and toluene. The collected experimental results were correlated to many models of isothermal adsorption. At all three temperatures the Langmuir models were modified to characterize the GAC adsorbing dichloromethane while the adsorptions of toluene to GAC were well-defined at all three temperatures by the Langmuir-BET hybrid model. Thermodynamic equation of Clausius–Clapeyron showing that the adsorption mechanism for both substances is endothermic was determined as well.